Introduction of Cut Nyak Dien's Figure in 2D Animation-Based Mobile Applications - Sabrina Az Zahrah; Syifa Hadiarti Aulia; Syifa Hanifa Wardani; Intan Permata Sari (Universitas Pendidikan Indonesia (UPI), 2023)
The introduction of National Indonesian heroes at this time is still a little using existing technology, where technology is currently developing rapidly. Making prototypes about Indonesian heroes is a form of appreciating, remembering and remembering the existing heroes. Thus, the design of the